Percutaneous removal of common bile duct stones using a modified balloon technique. Issue 14 (9th April 2021) - Kim, Yang Won; Lee, Sang Min; Choi, Ho Cheol; Won, Jung Ho; Na, Jae Boem; Cho, Jae Min; Choi, Dae Seob; Park, Mi Jung; Shin, Hwa Seon; Kim, Ji Eun; Park, Sung Eun; Shim, Jong Joon
Abstract : Abstract: To evaluate the effectiveness of percutaneous removal of common bile duct (CBD) stones using a modified balloon technique (balloon catheter sphincteroplasty and expulsion of the stones using half-captured balloons within the sheath) in patients difficult to treat with endoscopy. Fifty patients underwent a modified balloon technique (balloon group), and 53 patients underwent CBD stone removal by the basket method (stone basket group) between 2016 and 2019. We compared the balloon and stone basket groups to evaluate the effectiveness of the modified balloon technique. Outcome variables such as demographics, technical success rates, procedural details, and complications were analyzed. Statistical analysis was performed using Student t test, Fisher exact test, or the χ 2 test. The technical success rate in the balloon group was 66% (33/50) in 1 session, 32% (16/50) in 2 sessions, and 2% (1/50) in 3 sessions. That of the stone basket group was 45% (24/53) in 1 session, 38% (20/53) in 2 sessions, and 17% (9/53) in 3 sessions. The total procedure time was significantly shorter in the balloon group (29.5 ± 15.1 minutes) than in the stone basket group (41.7 ± 20.2 minutes) ( P < .01), whereas the number of stones was higher in the balloon group than in the stone basket group ( P = .03). Maximal stone size, balloon size, pancreatitis, and hospitalization stay did not show statistical differences between the 2 groups. Most complications (9 patients, balloon group; 8 patients, stone basket group) were mild and transient. Major complications occurred in one patient in the stone basket group, who experienced hemobilia due to arterial injury caused by percutaneous transhepatic biliary drainage, which was treated by endovascular embolization without mortality. The modified balloon technique is an effective and safe treatment method for CBD stone removal in patients presenting difficulties in the endoscopic approach.